2010
DOI: 10.1007/s12199-009-0129-2
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-linked immunosorbent assay of nicotine metabolites

Abstract: Introduction The level of cotinine in biological specimens, such as serum, urine, and saliva, measured by gas or liquid chromatography is the most validated and reliable indicator of exposure to tobacco smoke. However, chromatographic methods are not always suitable for all types of situations.Methods We validated a commercially available enzymelinked immunosorbent assay (ELISA) that uses a polyclonal antibody to cotinine as a practical alternative to chromatographic methods. Results The cotinine antibody cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 11 publications
0
30
1
Order By: Relevance
“…Both the GC/MS and HPLC/MS are accurate methods but may not be suitable for mass screening because they are expensive. In contrast, the high-sensitive ELISA method which we and Ohta first developed for clinical application is cheaper than GC/MS or HPLC/MS and can be used for analyzing many specimens at one time [13]. Therefore, it is considered suitable for mass screening.…”
Section: Discussionmentioning
confidence: 99%
“…Both the GC/MS and HPLC/MS are accurate methods but may not be suitable for mass screening because they are expensive. In contrast, the high-sensitive ELISA method which we and Ohta first developed for clinical application is cheaper than GC/MS or HPLC/MS and can be used for analyzing many specimens at one time [13]. Therefore, it is considered suitable for mass screening.…”
Section: Discussionmentioning
confidence: 99%
“…EIA can also be utilized in clinical settings to assess surrogate markers of smoking and the effects of nicotine drugs, such as NP. Hence, clinicians should carefully interpret the data obtained with immunoassay systems because the cross-reactivity for each immunoassay system differs (2). The antibodies may cross-react with compounds other than the measured nicotine metabolites (1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, his team proposed GC with nitrogen/phosphorus thermionic detection (GC-NPD) technique for chemical analysis and quantification of cotinine. This declaration was then confirmed by Watts and his fellow scientists in 1990, when they observed that there were no cross reactions that occurred, because the elements (nitrogen and phosphorus) in the cotinine molecule was itself used for detection (Matsumoto et al, 2010;Zuccaro et al, 1997;Watts et al, 1990). However, all the above mentioned methods are generally time consuming because sample extraction is done manually and they are expensive since they require trained expertise and costly reagents for equipment maintenance.…”
Section: Salivary Cotinine Detectionmentioning
confidence: 92%
“…For instance, in 1991 Hariharan and Van Noord developed gas chromatography on capillary column coupled to nitrogen phosphorus detector (GC-NPD) method to overcome cross reactivity that could occur in RLA methods. However, GC-NPD was found to have a lower detection limit as they are affected by certain drugs such as Theophylline if present in sample (Matsumoto et al, 2010;Kuo, Yang & Chiu, 2001;Feyerabend&Russel, 1990). Therefore, in 1998 Oddoze and his team developed reversed phase HPLC method paired with UV detector (RH-HPLC-UV), which is applicable for epidemiological studies.…”
Section: Urinary Cotinine Detectionmentioning
confidence: 99%